System and methods for identifying a subject through device-free and device-oriented sensing technologies - Martinez, Michel Allegue; Ghourchian, Negar; Jalil, Amir Minayi; Heidari, Sam (2024)
The systems and method proposed herein aim to identify a mobile device or devices worn by an individual or a subject that has entered an area monitored by a passive motion detection system that uses wireless signals to sense motion in the space. The system will collect as much signals as possible from both the devices worn by the individual and from the system performing the passive (device-free) motion detection for identifying the individual or person of interest. The individual or person of interest may be a user of a product or an intruder.